PETROGRAPHIC CHARACTERISTICS AND DEPOSITIONAL ENVIRONMENT OF COAL SEAMS D (MERAPI) AND E (KELADI), MUARA ENIM FORMATION, SOUTH SUMATERA BASIN - Asep Bahtiar Purnama; Nining Sudini Ningrum (Indonesian Mining Journal, 2012)
Coal seams D and E belong to the Muara Enim Formation in South Sumatra Basin, which includes to the Middle Miocene to Late Miocene. The research is located at the Air Laya coal mines, PTBA, Tanjung Enim, South Suma- tra. The purpose of this study was to investigate the characteristics of coal and coal depositional environments of Seam D (Merapi) and Seam E (Keladi). Observations were done on samples of coal from exploration drilling results from the Air Laya mining pit. The analysis is carried out by a petrographic analysis, which is supported by the results of coal vitrinite refl ectance.Petrographic characteristics indicate that both of seams D and E dominant macerals are vitrinite, the most dominant sub-group of vitrinite is telovitrinite. Inertinite in both seams consists of semifusinite, sclerotinite and inertodetrinite. Pyrite, clay mineral and carbonate are the main mineral in the seams. Vitrinite refl ectance (Rv- max,%) value shows similar rank of sub-bituminous to high volatile bituminous. Based on the results of coal depositional environment reconstruction using four parameters, which are the degree of preservation of plant tissue (TPI), the degree of Gelifi cation (GI), the degree of ground water infl uence (GWI) and vegetation aspects (VI), it is interpreted that seams D (Merapi) and E (Keladi) were deposited in upper delta plain depositional environment with ombrotrophic peat type.